Reindeer avoidance of pasture contaminated with sheep and reindeer faeces - Colman, Jonathan E.; Storlien, Svein; Moe, Stein R.; Holand, Øystein; Reimers, Eigil (Rangifer, 2003)
Contamination by excrements will increase in areas with high animal densities, such as snow free patches with accessible forage in winter and holding paddocks. Avoidance of faeces dropped by other grazers may result in interference competition by reducing optimal forage intake, or offer protection from the transfer of parasites or disease. We conducted two enclosure experiments investigating reindeer (Rangifer tarandus) reactions towards faeces. The first experiment tested whether reindeer avoid pasture contaminated with faeces from reindeer or sheep (Ovis aries). Both high (0.5 kg/m2) and low (0.05 kg/m2) concentrations of faeces reduced reindeer grazing compared to no faeces. Reindeer grazed significantly less in areas with high concentration of faeces compared to areas with low concentrations, with equally strong avoidance regardless of faeces source. The second experiment analysed the defecation pattern (random or not) of reindeer in a 50 m x 40 m enclosure to investigate how this pattern might change following the introduction of female sheep or additional female reindeer. Both reindeer and sheep defecated in a non-random pattern that was related to their preferred bedding sites. When sheep visited reindeer, the species' faeces distributions were positively correlated, indicating that reindeer and sheep had an overlap in area utilization, at least while bedding. When additional reindeer were introduced and then removed, the combined resident and visiting reindeers' faeces distributions were negatively correlated with the resident reindeers' faeces distribution following the removal of the visiting reindeer. This suggested that resident reindeer avoided the visiting reindeers' faeces. Resident reindeer also produced fewer total droppings when visited by new reindeer, while the number of droppings did not change when visited by sheep. Thus, resident reindeer were more adversely affected by the introduction of new reindeer even after their removal than by the introduction of sheep. In conclusion, the amount and distribution of excrements will play an important role in reindeer grazing and area use in pastures maintaining high densities of reindeer or reindeer and sheep.